Separation of Three Flavones from Chamaecyparis obtusa Using Functionalized Hollow Microsphere Polymers - Tian, Minglei; Bi, Wentao; Ho Row, Kyung (Asian Journal of Chemistry, 2014)
Soxhlet extractor was used to extract three flavones (quercitrin and myricetin and amentoflavone) from Chamaecyparis obtusa. A cartridge packed with sorbent was fixed at the end of the siphon side arm. The sorbent was used to absorb the target compounds during the extraction process. In order to obtain the highest separation efficiency, several functionalized ionic liquid-immobilized hollow microsphere polymers were investigated. Finally, the amino ionic liquid-immobilized hollow microsphere polymer with highly selectivity and stability achieved the purpose and 0.44 mg g-1 of quercitrin, 0.19 mg g-1 of myricetin and 0.12 mg g-1 of amentoflavone were obtained.